Dampak Kualitas Kehidupan Kerja dan Motivasi Kerja Terhadap Kinerja Tenaga Kependidikan IPB University - Firdha Juliantari; Widodo Sunaryo; Hari Muharam (IPB University, 2023)
The professionalism of Education staffs of IPB University is an important aspect in supporting higher education business processes to provide public services to stakeholders. Therefore, they need to have a good competence The purpose of this study is to analyze (1) the direct effect of quality of work life on the performance of education staffs, (2) the direct effect of work motivation on the performance of education staffs, and (3) the indirect effect of the variables on the quality of work life on the performance of the education staffs due to work motivation. The results of data processing on 222 research samples based on PLS-SEM concluded that the quality of work life has a direct and significant effect on the performance of education staffs, meaning that the performance of education staffs can be increased by improving the quality of work life. Work motivation has a direct effect on the performance of education staffs. It means that an increase in work motivation will boost the performance of education staffs. In addition, there is an indirect effect of the quality of work life on the performance of staff due to work motivation. The result found that there is a dirrect and indirect effect quality of work life on the performance without going trough or involving work motivation, so the role of this mediation is included in partial mediation where the independent variable was still able to directly influence the dependent variable without going through or involving the intervening variable.